CD82 Suppresses ADAM17-Dependent E-Cadherin Cleavage and Cell Migration in Prostate Cancer. (2nd November 2020) - Ma, Zhenkun; Gao, Ye; Liu, Wei; Zheng, Long; Jin, Ben; Duan, Bei; Xie, Hongjun; Guo, Peng; Zeng, Jin; Wang, Ke; Xu, Shan; Wang, Xinyang; et al.
Abstract : CD82 acts as a tumor suppressor in a series of steps in malignant progression. Here, we identified a novel function of CD82 on posttranslational regulating E-cadherin in prostate cancer. In our study, the declined expression of CD82 was verified in prostate cancer tissues and cell lines compared with normal tissue and cell lines. Functionally, CD82 inhibited cell migration and E-cadherin cleavage from the cell membrane in prostate cancer cell. Further study proved that a disintegrin and metalloproteinase ADAM17 as an executor of E-cadherin cleavage mediated the inhibitory regulation of CD82 in E-cadherin shedding in prostate cancer. Specifically, CD82 interacted with ADAM17 and inhibited its metalloprotease activity, which led to the descent of E-cadherin shedding. These results show a nuanced but important role of CD82 in nontranscriptional regulation of E-cadherin, which may help to understand the intricate regulation of dysfunctional adhesion molecule in cancer progression.